Differences in Employee Motivation in Wood-Processing Enterprises in Selected Countries of Central Europe - Hitka, Miloš; Ližbetinová, Lenka; Lejsková, Pavla; Nedeliaková, Eva; Sydor, Maciej (My University, 2023)
The human factor is still an irreplaceable element bearing a competitive advantage in the changed conditions of the wood-processing industry created by Industrial Revolution 4.0. Their sophisticated use and motivation result in the company's higher performance potential, and satisfaction is reflected in higher employee loyalty. The study aims to evaluate the level of motivation of employees working in the wood-processing industry in selected Central European countries (Slovakia, the Czech Republic, and Ukraine) from the point of view of groups of motivation factors and then to compare them between countries in terms of gender and age. Differences in the mean values of the compared groups were tested, taking into account the confidence interval. The research was conducted at the beginning of 2021 when Ukraine has not been in a military conflict yet. The result of our findings is the knowledge that the most important motivation factors for Slovak employees in the wood-processing industry are those related to finance and employer-employee relationships. Czech employees also prefer the same motivation factors but place less emphasis on them. Employees of the wood-processing industry in Ukraine prefer motivation factors related to finance and career aspiration. From the point of view of motivation, the input qualitative parameters of rawwood material and its assessment in forest stands are also important. In globalization, the findings of our study can serve as insights for managers within the wood-processing industry. These insights can be particularly beneficial in enhancing the quality of human resource management, with a particular emphasis on bolstering employee motivation.
Rozdíly v motivaci zaměstnanců v dřevozpracujících podnicích ve vybraných zemích střední Evropy
Keywords: motivation factors; differences in employee motivation; salary; career aspiration; work conditions; workplace well-being factors; social needs; wood-processing industry; Slovak Republic; Czech Republic; Ukraine; motivační faktory; rozdíly v motivaci zaměstnanců; odměňování; pracovní podmínky; sociální potřeby; Slovensko, Česká republika, Ukrajina